Fenomena Avatar Sebagai Subjek Hukum Di Metaverse - Andreas Tedy Mulyono; Eka NAM Sihombing (Jurnal Ilmiah Penegakan Hukum, 2023)
The problematics of IT innovation that develops the metaverse as a medium of interaction is a social phenomenon that needs to be studied immediately. As a popular three-dimensional social media, the metaverse can shift from a societal problem to a social problem where legal norms are needed. The problem is how elements of the legal system can work together to anticipate social changes driven by such technological developments. The research method used is normative juridical which analyzes stable socio-legal concepts and related laws and regulations. This study concludes that Avatar as a legal subject in the metaverse requires a legal system that simultaneously regulates the life of the Avatar in the metaverse and the life of its owner in the real world. The recommendation for this study is that practically in the litigation process, Avatar's criminal disputes in the metaverse can apply complaint offenses as a limitation of law enforcement in the real world for the sake of legal certainty and community justice